The connotation, cause, and reform path of institutional transaction costs: a grounded theory analysis - Zeng, Zhaoteng; Yu, Xiao (Local government studies, 2024)
Institutional transaction costs profoundly reflect the relationship between the government and the market, and play an important role in the economic development of a country or region. This study uses grounded theory to explore its theoretical connotation and essential reasons, confirms the core elements from the three dimensions of subject, behaviour and environment, and then builds its theoretical framework. The results show that, under the influence of bounded rationality and opportunism, institutional transaction cost is a kind of cost generated by market players in the process of complying with government economic policies. Therefore, this study attempts to provide a reference path for institutional transaction cost reforms in other countries or regions from three aspects: improving the efficiency of government agencies, regulating government regulatory behaviour, and improving the institutional environment of the market.